Research on bond-slip behavior of corroded square rebar-concrete in historical reinforced concrete buildings - Zhendong Mi; Qing Chun; Hui Jin; Chengwen Zhang; Jiashun Shi (Case Studies in Construction Materials, 2024)
Corrosion of rebar often leads to the degradation of the bond-slip performance of reinforced concrete members, which is a serious issue in historical buildings. The bond-slip behavior of square rebar, which is widely used in historical reinforced concrete buildings, is significantly different from that of round rebar. In this paper, a bond-slip model of corroded square rebar reinforced concrete was developed. First, 18 square rebar reinforced concrete cube pull-out specimens are made, and the corrosion of rebars is accelerated by electrochemical corrosion experiments. Second, a universal global optimization method was used to construct the bond slip expression and the four-fold line bond-slip model with different corrosion rates was obtained by using the minimum Euclidean distance point. Third, the calculation formulas for the bond strength reduction coefficient and slip ratio of corroded square rebar-concrete in historical reinforced concrete buildings are derived. Finally, the bond-slip constitutive model of corroded square rebar-concrete in historical reinforced concrete buildings is established. The results show that the model is more accurate, simple, effective, and easy to use in practical engineering. The research results provide an important theoretical basis for the structural evaluation and conservation of historical reinforced concrete buildings.